DAVR ADABIYOTIDA AMIR UMARXON FENOMENI - Juraboev , Otabek (Educational Research in Universal Sciences, 2023)
The article talks about the role of the Kokand Khan and the talented poet Amir Umarkhan in Uzbek literature of the 19th century. Examples are given that he is an organizer of the literary environment, a major representative and one of the brightest literary figures of that time, and a skilled lyricist. The classification is presented with the help of various examples and facts.